Aesthetic Preference in the Spatial Composition of Traditional Chinese Paintings. (May 2015) - Zheng, Lu; Weidong, Zhang; Xuchen, Gao
Aesthetic psychology has discussed many aspects of aesthetic preferences for spatial composition. However, there have been few empirical explorations of the spatial composition of traditional Chinese paintings. The results of this experiment showed that the shape of the frame had a significant effect on aesthetic preferences. Participants preferred to put two figures at certain relative horizontal distances from each other according to the horizontal shape of the frame but may have difficulty in adapting the relative vertical distance according to the vertical shape of the frame. Furthermore, the unique aesthetic interest of traditional Chinese long-vertical scroll paintings was discussed. This discussion revealed that, in a creative way, ancient Chinese artists followed the same aesthetic principles we observed, and they developed the artistic conception and romantic charm of traditional Chinese paintings.